Interaction between occupational radon exposure and tobacco smoke: a systematic review. Issue 7 (3rd July 2022) - Folesani, Giuseppina; Galetti, Maricla; Ranzieri, Silvia; Petronini, Pier Giorgio; La Monica, Silvia; Corradi, Massimo; Cavallo, Delia
ABSTRACT: Introduction: The risk of lung cancer from radon exposure was small compared to tobacco smoking (BEIR VI), but the relationship between these two carcinogenic agents has yet to be quantitatively estimated. The objective of this systematic review was to evaluate the last evidences on the role of radon occupational exposures and tobacco smoke on lung cancer risk. Areas covered: Thirteen articles were selected using two different databases, PubMed and Scifinder, and were limited to those published from 2010 to 2021. The reference list of selected studies was reviewed to identify other relevant papers. Expert opinion: Seven papers included in this systematic review did not deal with the multiplicative or the additive type of interaction between radon exposure and smoking habit. Six papers discussed the nature of this interaction with a prevalence of the sub-multiplicative model compared to the additive one. Altogether, smoking adjustment did not significantly change lung cancer risk. The included studies might constitute a starting point for updating the models for risk assessment in occupational and residential scenarios, promoting concomitantly the exposure reduction to radon and other cofactors, as recently introduced by Italian Legislative Decree number 101 of 31 July 2020, an application of Euratom Directive 59/2013. Plain Language Summary: This paper offers an updated overview on lung cancer risk due to occupational exposure to radon together with tobacco smoking habits. It evidences the quantitative role of smoking on radon exposure and discusses their interaction. The results show that smoking adjustments do not significantly modify lung cancer risk at both high and low radon concentrations.